EVALUATION OF HEAVY METALS' CONCENTRATION AND PHYSICOCHEMICAL PARAMETERS OF GROUNDWATER WITHIN JOS METROPOLIS OF PLATEAU STATE, NIGERIA - Yusuf, James; Kalip, Aminu; Aremu, S. O. (FUDMA JOURNAL OF SCIENCES, 2024)
This paper studied the quality of drinking water from borehole sources in Jos and its environs. The level of heavy metal concentrations and some physicochemical parameters were determined using standard methods. The result of heavy metal concentrations analyzed within the ten (10) sampling points shows that JS1 sampling point had a significantly high (p<0.05) concentration of copper (0.0064 mg/L) and lowest in JS1 sampling point (0.001 mg/L). Chromium had a significantly high (p<0.05) concentration in JS10 sampling point (0.718 mg/L) and lowest in JS1 (0.153 mg/L).  Manganese had significantly high (p<0.05) concentration in JS4 sampling point (0.198 mg/L) and lowest in (JS6 0.020 mg/L). Iron was significantly high (p<0.05) in JS4 sampling point with the concentration of 1.388 mg/L and lowest value of 0.020 mg/L in JS5. Zinc had a significantly high (p<0.05) in JS4 sampling point with the concentration of 0.085 mg/L. Lead had significantly high (p<0.05) in JS8 sampling point with a concentration of 0.005 mg/L. Cadmium and nickel were not detected in all ten (10) sampling points. The electrical conductivity and pH and were found to be in the range of (0.000 - 350 µSv/cm) and (4.81 – 6.70), respectively. This research findings suggest that continued water quality monitoring should be carried out to check the concentration levels of copper, zinc, manganese, cadmium, nickel, lead and physicochemical parameters electrical conductivity and pH in those ten (10) sampling points to prevent them from been above the limit of World Health Organization (WHO) permissible limit and also creating...